(untitled) (Jurnal Manajemen Bisnis, 2026)
This research aims to analyse the influence of market orientation and innovation on marketing performance, mediated by business agility, in MSMEs in Dompu Regency. In the VUCA era, MSMEs face intense competitive pressures and shifts in consumer behaviour, raising the question: can innovation and market orientation boost performance without operational agility? The novelty of this research lies in testing the mediating effect of business agility to address inconsistencies in prior literature on the innovation paradox, which often burdens the performance of resource-limited MSMEs in developing countries. Using a quantitative approach, data were collected from 252 MSME managers in the food and beverage sector through purposive proportional random sampling, then analysed using Structural Equation Modelling (PLS-SEM). Empirical results show that market orientation positively affects marketing performance, whereas innovation does not have a significant direct impact. The discussion of the findings confirms that business agility plays a vital role in fully mediating the relationship between innovation and partially mediating the effect of market orientation on performance. In conclusion, innovation will be commercially valuable only if it transforms MSMEs into agile entities. From a managerial perspective, government and business intervention must be reoriented from merely ceremonial new-product launches to incubation programs that increase managerial flexibility and supply-chain adaptability.